2012
DOI: 10.1108/13665621211209285
|View full text |Cite
|
Sign up to set email alerts
|

Charting collective knowledge: supporting self‐regulated learning in the workplace

Abstract: Purpose -This study aims to outline an approach to improving the effectiveness of work-based learning through knowledge creation and enhancing self-regulated learning. The paper presents a case example of a novel approach to learning through knowledge creation in the workplace. This case example is based on empirical data collected through a study of the learning practices of knowledge workers employed within a large, multinational organization. Design/methodology/approach -The case example presented in this a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(80 citation statements)
references
References 9 publications
2
77
0
1
Order By: Relevance
“…Informal learning at work is recognized as a key component in CPD (Cheetham & Chivers, ). Informal learning has been gaining in prominence as increasingly specialized, distributed and changing work practices require professionals to solve novel problems, identify what they need to know and recognize where they can obtain the necessary information or how they may create new knowledge (Littlejohn et al ., ; Margaryan, ). In contrast to formal learning settings where learning goals and pathways to achieving these are explicitly defined, in informal WPL contexts professionals have to engage in self‐regulation to articulate and pursue their learning goals.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Informal learning at work is recognized as a key component in CPD (Cheetham & Chivers, ). Informal learning has been gaining in prominence as increasingly specialized, distributed and changing work practices require professionals to solve novel problems, identify what they need to know and recognize where they can obtain the necessary information or how they may create new knowledge (Littlejohn et al ., ; Margaryan, ). In contrast to formal learning settings where learning goals and pathways to achieving these are explicitly defined, in informal WPL contexts professionals have to engage in self‐regulation to articulate and pursue their learning goals.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another possible explanation was that participants changed or refined their goals during the learning process as evidenced in prior studies (Kizilcec et al, ; Littlejohn et al, ). Their learning goals were adjusted when they gained a deeper understanding of the new system, and found a balance of their efforts between the learning and other situational factors.…”
Section: Discussionmentioning
confidence: 97%
“…However, existing studies did not reach consistent conclusions on how employees (un)successfully learned towards those goals and what factors acted on this effort (Margaryan, Littlejohn, & Milligan, ; Yelich Biniecki, ). In addition, Littlejohn, Milligan, and Margaryan () pointed out that it was challenging to measure learners' attainment of goals as they were not pre‐defined. Their study gathered 29 interviews from 12 companies and results showed those goals were adjusted in the learning process because of learners' interaction with learning content, environment, and peers (Margaryan, Littlejohn, & Milligan, ).…”
mentioning
confidence: 99%
“…Some of the interventions offered through the system, such as the provision of usage information on resources in the system, or the recommendation of competences or learning goals or paths, can be considered to be based on emergent knowledge structures (Siadaty, Gašević, & Hatala, 2016). The Charting Collective Knowledge model proposed by Littlejohn, Margaryan, and Milligan (2012) is also situated in the self-regulated learning literature, and individual learning is seen as being influenced by collective knowledge (structures) to which individuals contribute.…”
Section: Related Approachesmentioning
confidence: 99%